Sarcoidosis Manifested as Recurrent Pericardial Effusion with Signs of Impending Tamponade - Christine Elizabeth Suryajaya; Susantina Prodjosoewojo; Arto Y. Soeroto; Nuraini Yasmin Kusumawardhani; Rudi Supriyadi; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2022)
Pericardial effusion is a fatal and life-threatening condition. If it is not addressed thoroughly, complications such as constrictive pericarditis may occur. Etiologies of pericardial effusion varied and one of the most common etiologies is tuberculosis. Other etiologies include inflammation, malignancy or other autoimmune disorder such as sarcoidosis. Sarcoidosis is a diagnosis of exclusion and is confirmed by biopsy result that showed non-caseating epitheloid-cell granuloma, with no other organism or particles. Epidemiology of sarcoidosis in Japan is 1-2 case per 100.000 patients, with the peak incidence between the age of 20 to 39 years old. We reported a case of 37 years old woman presented to our emergency department with shortness of breath and signs of pericardial tamponade. She was previously healthy with no other significant past medical. She was first treated as a case of extrapulmonary tuberculosis and shown no improvement with anti-tuberculosis medications. Several work ups were then done in search of other etiologies of her pericardial effusion. A biopsy form one of her abdominal lymph nodes was performed, which pathologically revealed sarcoidosis. She was placed on corticosteroid and methotrexate with improvement of symptoms. One month followed up showed complete resolution of her pericardial effusion.